2017
DOI: 10.1590/2317-1545v39n4181134
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic stress on genetically transformed tobacco plant seeds

Abstract: -Salinity and water deficit limit the productivity of several crops; thus, studies related to the genetic transformation of seeds in a model plant, such as tobacco, can be an alternative to minimize negative impacts caused by environmental conditions. The purpose of this work was to evaluate the tolerance to osmotic stress of seeds from genetically transformed tobacco plants, with the introduction of the proline-synthesizer gene (p5csf129a), under salinity and water deficit conditions. To do so, five events wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…To observe the germination of transgenic tobacco seeds under salt stress, T1 seeds were germinated on filter paper and cotton moistened with salt solution (200mM NaCl), and the germination rate was calculated after 12 days. The NaCl concentration used in the treatment was referred to the previous study (Trombin-Souza et al, 2017;Tok and Temizel, 2021).…”
Section: Plant Materials and Experimental Designmentioning
confidence: 99%
“…To observe the germination of transgenic tobacco seeds under salt stress, T1 seeds were germinated on filter paper and cotton moistened with salt solution (200mM NaCl), and the germination rate was calculated after 12 days. The NaCl concentration used in the treatment was referred to the previous study (Trombin-Souza et al, 2017;Tok and Temizel, 2021).…”
Section: Plant Materials and Experimental Designmentioning
confidence: 99%
“…We also observed that embryos under desiccation had an increase in Glu and Gly content by 30 and 6-fold, respectively. Glutamic acid is a precursor of Pro and their high concentration was associated to wild chickpea drought-tolerant seeds (Behboudian et al 2001;Rontein et al 2002;Trombin-Souza et al 2017). Like Glu, the Gly is also indirectly related to desiccation tolerance, since one of the glycinebetaine (GB) synthesis pathways is through glycine Nmethylation Murata 2002, 2011).…”
Section: ) It Was Reported That Glycerol and Sucrose Led To Increased Vacuolization And Autophagy In Haemanthus Montanusmentioning
confidence: 99%